Perubahan Nilai Anak di Banyumas: Sebuah Ulasan Sosiologis - Arizal Mutahir; Elis Puspitasari; Rin Rostikawati; Wiman Rizkidarajat; Alfian Ihsan (Jayapangus Press, 2023)
Various social changes were taken place in Banyumas, as in other regions. The changes directly or indirectly affected to the smallest unit of society, the family. There was a shifting in the values believed and practiced by the family due to the changes, including the value of children. Regarding on these condition, the paper has purposed to explore parents' worldviews on children's value in Banyumas. The children's value is the utility of children to parents or the needs that able to be fulfilled by children for parents. Employing a qualitative approach, the paper attempted to explore the value of children for parents in rural Banyumas. Observation, interview and documentation techniques were used to collect the data. There were twenty-eight informants as the source of primary data. Purposive technique was used to determine of informants. Triangulation technique was used to validate the data. Data analysis was conducted interactively. The study found that the value of children for parents in rural Banyumas was dominated by economic value. The parents placed children as material assets and put their children's in school to have quality improvement. Parents did not differentiate between girls and boys. It was a reflection of the egalitarian attitude of Banyumas culture. This research found that there has been a displacement in the allocation of needs, it was a displacement from costs allocation for food to costs allocation for children's education.